Alternatives to the proposed taxation of retirement fund interests on emigration from South Africa - Adams, Taryn (Department of Finance and Tax, 2025)
The 2021 Budget Speech, as well as the 2021 draft Taxation Laws Amendment Bill, included a proposal from National Treasury to implement an “exit tax” on retirement fund interests for resident individuals who emigrate from South Africa (i.e., become non-resident for tax purposes). The proposal, however, raised numerous concerns amongst experts in the industry, which ultimately led to its withdrawal in November 2021. While National Treasury indicated an intention to re-design the proposal, there has been no update since that time. This study addressed two research objectives. Firstly, it investigated the policy objectives and shortcomings of the initial proposal which ultimately led to its withdrawal. Secondly, it addressed how the approach might be re-designed by considering alternatives that would achieve the objectives of the original proposal without its shortcomings. This is a relatively new area of research with no previous published work performed on the topic (to the author's knowledge), emphasizing the relevance and significance of this study. This study was performed using a combination of doctrinal and non-doctrinal legal interpretative research methods. Doctrinal legal research was used to obtain an understanding of the prevailing legislative framework and the initial proposal from National Treasury. Non-doctrinal legal research was used to consider alternative approaches in the re-design process. The criteria for an alternative approach included the potentially competing needs for 1) equity within, 2) economic efficiency of, 3) administrability of, and 4) coherence of the tax system. The study explored four possible alternative approaches, each of which have some merits and some shortcomings. It concluded that one feasible alternative could be to migrate the retirement funding tax system to one in which contributions are afforded no tax incentives and retirement benefits are received free of taxation. However, this would be a radical departure from the existing approach, introduce more complexity into a system that is already dealing with the transitional provisions of several significant upheavals in the last few years, and would be complicated to manage on an ongoing basis. The other three alternatives considered would be less radical but would not be as effective in satisfying the evaluation criteria. National Treasury would need to weigh up whether the policy objectives and protection of the South African tax base are worth dealing with these challenges.